Persepsi Anggota Gapoktan “Karya Tani” Pada Pupuk Organik Komsah - Nur Alif, Muhammad Gilang; Suminah, Suminah; Widiyanti, Emi (Jurnal Sosial Ekonomi Pertanian, 2024)
The research is aimed at finding out the perception of members of the Gapoktan "Karya Tani" to Komsah organic fertilizer in Tasikmadu district, Karanganyar district. The study used a survey method with respondents of 65 farmers who were included in the "Tani Karya" Gapoktan. The results of the research show that the majority of farmers have a low level of non-formal education and are not actively engaged in nonformal educational activities. Farmers' perceptions of Komsah organic fertilizer generally have different scores, with relative advantages equal to good, poor complexity, good triability, and poor observability. Double linear regression analysis shows that non-formal education variables and practical experience have a significant influence on farmers' perceptions of Komsah organic fertilizer. The results of this study show that nonformal learning and practicality experience influence farmers’ perceptions about Komsah Organic Fertilizer, and that farmers who have a higher level of informal education and longer practical experiences tend to have a more positive perception of Komah organic fertilizers.